The Influence of Project-Based Learning in Improving Students' Critical Thinking Skills in Science Subjects in Elementary Schools - Alpha Alpha; Baharuddin Baharuddin; , Ilham Assidiq (Universitas Muhammadiyah Enrekang, 2024)
Effective learning methods play an important role in developing students' critical thinking skills. This study aims to analyze the effect of project-based learning methods on elementary school students' critical thinking skills. A quantitative approach with experimental design was used in this study, involving two groups of students, namely the experimental group using project-based learning methods and the control group using conventional methods. Data were collected through critical thinking tests and analyzed using statistical tests. The results showed that students who studied with project-based learning methods had higher critical thinking scores compared to the control group. This indicates that project-based learning methods can improve students' critical thinking skills by providing more active, contextual, and collaborative learning experiences. Thus, this method can be an effective alternative in improving the quality of learning in elementary schools.